Delimitation procedure of degraded areas and the area targeted for revitalisation - Raszkowski, Andrzej; Sobczak, Elżbieta (Economics of the 21st Century, 2018)
The study discusses problems related to identifying degraded areas and the area targeted for revitalisation in relation to the local government units (cities, municipalities, regions). The core part of the study presents an example of the typology of factors and crisis phenomena in a social, economic, spatial-functional, environmental and technical perspective. The delimitation procedure, based on the application of indicators describing the concentration of phenomena in the system of municipal urban units was discussed. Next the area targeted for revitalisation was characterised as part of the identified degraded areas. This was followed by characterising the degraded areas based on the conducted survey studies. In both cases the delimitation procedure is covered by a civic control scheme. Within the framework of general conclusions it can be adopted that the described procedures or similar ones are most frequently applied in relation to Polish local government units
Ekonomia XXI Wieku = Economics of the 21st Century, 2018, Nr 2 (18), s. 30-38
Keywords: revitalisation; delimitation procedure; socio-economic development; development policy; degraded area; rewitalizacja; procedura delimitacji; rozwój społeczno-ekonomiczny; obszar zdegradowany; obszar rewitalizacji